Alteration of the Interconversion of Pyruvate and Malate in the Plastid or Cytosol of Ripening Tomato Fruit Invokes Diverse Consequences on Sugar But Similar Effects on Cellular Organic Acid, Metabolism, and Transitory Starch Accumulation. - Osorio-Algar, Sonia; Vallarino, José G.; Szecowka, Marek; Ufaz, Shai; Tzin, Vered; Angelovici, Ruthie; Galili, Gad; Fernie, Alisdair R. (Oxford Academic, 2012)
The aim of this work was to investigate the effect of decreased cytosolic phosphoenolpyruvate carboxykinase (PEPCK) and plastidic NADP-dependent malic enzyme (NADP-ME) on tomato (Solanum lycopersicum) ripening. Transgenic tomato plants with strongly reduced levels of PEPCK and plastidic NADP-ME were generated by RNA interference gene silencing under the control of a ripening-specific E8 promoter. While these genetic modifications had relatively little effect on the total fruit yield and size, they had strong effects in fruit metabolism. Both transformants were characterized by lower levels of starch at breaker stage. Analysis of the activation state of ADP-glucose pyrophosphorylase correlated with the decrease of starch in both transformats, which suggest that is due to an altered cellular redox status. Moreover, metabolic profiling and feeding experiments involving positional labelled glucoses of fruits lacking in plastidic NADP-malic enzyme and cytosolic PEPCK activities revealed differential changes in overall respiration rates and tricarboxylic acid (TCA) cycle flux. Inactivation of cytosolic PEPCK affected the respiration rate which suggests that excess of oxaloacetate OAA is converted to aspartate and reintroduced in the TCA via 2-oxoglutarate/glutamate. On the other hand, the plastidic NADP-malic enzyme antisense lines were characterized by no changes in respiration rates and TCA cycle flux and together with an increase of pyruvate kinase and phosphoenolpyruvate carboxylase activities indicates that pyruvate is supply through these enzymes to the TCA cycle. These results are discussed in the context of current models of the importance of malate during tomato fruit ripening.
Keywords: Tomates - Maduración; Plantas - Metabolismo; Tomates - Ingeniería genética; Tomato; Fruit; Cytosolic phosphoenolpyruvate carboxykinase; Plastidic NADP-dependent malic enzyme